2011
DOI: 10.1007/s12686-010-9379-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterisation of novel microsatellite loci for the baldchin groper (Choerodon rubescens) and cross-amplification in seven other labrid species

Abstract: 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 2 Abstract 42We describe the development and characterisation of novel microsatellite loci for the baldchin groper, 43Choerodon rubescens. The purpose was to identify loci that can be used to resolve uncertainties about 44 the population (stock) structure of this fish species, which is endemic to a narrow region of the west 49Cross-amplification of the 12 loci in 7 other labrid species was often successful, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
(9 reference statements)
1
7
0
Order By: Relevance
“…Although the time periods covered preclude investigation across multiple generations, they are adequate for assessing interpopulation migration and population range shifts as a result of temporal variation in recruitment or population density (information important in fisheries management). The Cockburn Sound samples were collected by DPIRD WA staff as part of a fisheries independent survey, while the Esperance samples were collected by DPIRD WA staff from commercial catch for a former population genetics project (see Gardner et al, 2014Gardner et al, , 2017Gardner & Chaplin, 2011).…”
Section: Sampling and Associated Biological Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the time periods covered preclude investigation across multiple generations, they are adequate for assessing interpopulation migration and population range shifts as a result of temporal variation in recruitment or population density (information important in fisheries management). The Cockburn Sound samples were collected by DPIRD WA staff as part of a fisheries independent survey, while the Esperance samples were collected by DPIRD WA staff from commercial catch for a former population genetics project (see Gardner et al, 2014Gardner et al, , 2017Gardner & Chaplin, 2011).…”
Section: Sampling and Associated Biological Informationmentioning
confidence: 99%
“…Recent mark‐recapture work on the lower west coast of WA indicated that adult movement is largely limited to spatial scales of <20 km, although this estimate is probably influenced by spatial variability in fishing effort (Crisafulli et al, 2019). Microsatellite DNA analyses have suggested that snapper in WA are characterized by an isolation by distance pattern of population structure, rather than genetically distinct subpopulations (Gardner & Chaplin, 2011). Otolith microchemistry studies have reported different patterns of mixing during different life stages as well as a range of patterns of spatial differentiation using different chemical tags (Edmonds et al, 1999; Fairclough et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The PCR protocols, primer sequences and locus characteristics are as described by Gardner et al (2011).…”
Section: Molecular Analysesmentioning
confidence: 99%
“…Unless otherwise stated, methods were as described in Gardner et al (2011). Four partial genomic libraries, enriched for TAGA, CAGA, CA and ATG motifs, were constructed.…”
mentioning
confidence: 99%
“…Primer pairs were designed for 35 loci. The PCR mixtures were as per Gardner et al (2011) except for different concentrations of Taqpolymerase (0.25 U), dNTPs (0.1 mM), and primers (0.02 µM for the forward and M13A or M13B primers and 0.04 µM for the reverse).…”
mentioning
confidence: 99%